Leveraging Data Analytics for Effective Public Relations Practice in Nigeria Customs Service - Maiwada, Abdullahi Aliyu; Adeogun, Folusho; Muhammad, Aliyu (Budapest International Research and Critics University, 2025)
In today’s digital age, data analytics has become a powerful tool for enhancing public relations (PR) strategies, especially in public sector institutions like the Nigeria Customs Service (NCS). This study explores the role of data analytics in enhancing public relations (PR) practices within the Nigeria Customs Service (NCS). As public institutions face growing demands for transparency, accountability, and stakeholder engagement, the integration of data-driven strategies in PR becomes increasingly vital. This research examines how data analytics tools and techniques can support the NCS in monitoring public sentiment, evaluating communication effectiveness, managing crises, and shaping strategic messaging. Using content analysis data from media sources, and operational metrics, the NCS can foster a more responsive and informed public relations framework. The paper highlights case examples, identifies current challenges, and offers recommendations for institutionalizing data analytics in PR operations to build trust, improve public perception, and support organizational goals within the broader context of digital governance in Nigeria. The paper concludes that in an era where data-driven decision-making defines institutional credibility and stakeholder engagement, the Nigeria Customs Service stands to gain significantly by integrating data analytics into its public relations practice.